(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This article analyzes Ho Chi Minh’s thought on political power control, viewing it as the foundation for building a socialist rule-of-law state, aimed at preventing and combatting the degradation of power and the scourge of corruption. Based on the examination of the concept, objectives, content, and methods of power control, the article clarifies the theoretical and practical significance of Ho Chi Minh’s thought in ensuring that political power always serves the interests of the people, and does not become a tool for individual or group interests. The application of this thought has profound practical guidance value for the work of anti-corruption in Vietnam, to ensure the mastery of the people in the country’s current new era of development.